Comparative Study of Water Desalination using Reverse Osmosis (RO) and Electro-dialysis Systems (ED): Review (Journal of Engineering, 2023)
The increasing drinking water demand in many countries leads to an increase in the use of desalination plants, which are considered a great solution for water treatment processes. Reverse osmosis (RO) and electro-dialysis (ED) systems are the most popular membrane processes used to desalinate water at high salinity. Both systems work by separating the ionic contaminates and disposing of them as a brine solution, but ED uses electrical current as a driving force while RO uses osmotic pressure. A direct comparison of reverse osmosis and electro-dialysis systems is needed to highlight process development similarities and variances. This work aims to provide an overview of previous studies on reverse osmosis and electro-dialysis systems related to membrane module and design processes; energy consumption; cost analysis; operational problems; efficiency of saline removal; and environmental impacts of brine disposal. RO system uses osmotic pressure as a driving force to force water through the membrane with less energy than other desalination systems. The enhancements in membrane materials and power recovery of the unit have massively decreased the price of RO units. ED system uses an electrical current to push dissolved ions across ion exchange membranes. The results of this review showed that desalination plants must be integrated with renewable energy to reduce power consumption and costs related to energy. Various technologies, including treatment processes and disposal methods, must be used to control concentrated solutions resulting from desalination processes because 5 to 33% of the total cost of the desalination process is associated with brine disposal.